Adaptive Interactions between HLA and HIV-1: Highly Divergent Selection Imposed by HLA Class I Molecules with Common Supertype Motifs - John, Mina; Heckerman, David; James, Ian; Park, Lawrence P.; Carlson, Jonathan M.; Chopra, Abha; Gaudieri, Silvana; Nolan, David; Haas, David W.; Riddler, Sharon A.; Haubrich, Richard; Mallal, Simon (The Journal of Immunology, 2010)
Currently, 1.1 million individuals in the United States are living with HIV-1 infection. Although this is a relatively small proportion of the global pandemic, the remarkable mix of ancestries in the United States, drawn together over the past two centuries of continuous population migrations, provides an important and unique perspective on adaptive interactions between HIV-1 and human genetic diversity. HIV-1 is a rapidly adaptable organism and mutates within or near immune epitopes that are determined by the HLA class I genotype of the infected host. We characterized HLA-associated polymorphisms across the full HIV-1 proteome in a large, ethnically diverse national United States cohort of HIV-1–infected individuals. We found a striking divergence in the immunoselection patterns associated with HLA variants that have very similar or identical peptide-binding specificities but are differentially distributed among racial/ethnic groups. Although their similarity in peptide binding functionally clusters these HLA variants into supertypes, their differences at sites within the peptide-binding groove contribute to race-specific selection effects on circulating HIV-1 viruses. This suggests that the interactions between the HLA/HIV peptide complex and the TCR vary significantly within HLA supertype groups, which, in turn, influences HIV-1 evolution.